THE IMPORTANCE OF INNOVATIVE METHODS IN FORMING SPIRITUAL AND MORAL EDUCATION OF SECONDARY SCHOOL STUDENTS - Xatamova Ma’rifat Yorkinovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: This article examines the importance of innovative teaching methods in shaping the spiritual and moral education of students in general secondary education institutions. In the context of modern educational reforms, there is an increasing need to implement effective and student-centered approaches that foster ethical values and personal development. The study employs a mixed-methods approach to analyze the impact of innovative methods on students’ engagement, academic performance, and moral development. The findings reveal that the use of innovative strategies significantly enhances students’ interest, promotes independent thinking, and strengthens the internalization of moral values. The article concludes that innovative methods are a key factor in improving the quality and effectiveness of spiritual and moral education in secondary schools.